Penguatan Karakter Santri di Era Digital Melalui Tradisi Kajian Tafsir Al-Qur’an - Rini Fitriani Permatasari; Ibnu Khaldun; Sinthia Widhi Zahidah; Muhammad Faisal (Scidacplus, 2026)
The tradition of studying the interpretation of the Qur'an has long been one of the main foundations of pesantren education. Through this tradition, the scientific heritage of Islam continues to be maintained, as well as a means of shaping the character of the students. However, the presence of the digital era brings new challenges that cannot be ignored, especially changes in learning methods and the rush of religious information that does not always have clear authority. This research aims to describe how the tradition of tafsir study is carried out at Pondok Ahlus Suffah Hidayatullah Balikpapan and how this tradition plays a role in shaping the character of students in the midst of the dynamics of today's digital life. Using a qualitative-descriptive approach, data were collected through observation, in-depth interviews, and documentation at Pondok Ahlus Suffah Hidayatullah Balikpapan. The results of the study show that the Islamic boarding school still maintains the tradition of studying tafsir through routine halaqah, reading the book, and fostering adab. The study of tafsir is not only a space for knowledge transfer, but also a process of instilling Qur'anic values such as discipline, simplicity, and responsibility. On the other hand, Islamic boarding schools respond to digital challenges by strengthening digital literacy, limiting the use of gadgets, and selectively utilizing technology as a complement to learning. The findings of this study confirm that the tradition of interpretation studies remains relevant and plays an important role in shaping the character of students. This tradition has proven to be able to adapt wisely to digital developments without losing the scientific spirit and values inherited from generation to generation.